The results of open observational trial DIAMOND - Marina Vladimirovna Shestakova (Endocrinology Research Centre, 2011)
Aim. DIAMOND (DIAMicrON in Daily practice) is an open non-randomized observational trial aimed to estimate the efficacy and safety of gliclazide(Diamicron MB) in routine clinical practice. Materials and methods. 394 patients with poor control of type 2 diabetes mellitus (T2 DM), previously treated with diet or one of oral antidiabeticdrug (OAD), were switched to Diamicron MB. Previous therapy was left unchanged, except for a sulfonylurea or glinide that were canceled. Results. After 6 months of Diamicron MB therapy (30% monotherapy, 70% combined therapy) target HbA1c